Gettıng on Board wıth Robotıc Process Automatıon (Rpa) - A Study on the Benefıts of RPA - Madhusree Prakash, (International Journal of Advanced Science and Technology, 2020)
The nature of work keeps changing thanks to automaton and digitization. More companies are now techno savvy and are keen to adopt robotic process automation (RPA) as a tool with a view to streamline operations and decrease avoidable costs and overheads. With RPA, companies can automate routine rules-based business processes, allowing them to pay more attention for other non-repetitive and challenging tasks. Others see RPA as a steppingstone waiting to adopt and implement intelligent automation (IA) via machine learning (ML) and artificial intelligence (AI) tools. More and more companies undertake process re-engineering which effectively means reinventing the job they do and therefore organizations should continuously keep working on how jobs can be designed, and work organized to plan for future growth. To stay competitive, companies should stay informed about technological development and drive such changes in order to revamp the processes and automate them. Processes are of different types – some are highly customized necessitating human intervention while others are mostly repetitive, mature and stable but voluminous. While RPA tools may not suit highly customized processes, these are best suitable for processes with repeatable, foreseeable interactions with IT applications and which normally lack the size or value warranting full scale core IT solutions. RPA tools seek to enhance the efficiency/effectiveness of these processes /services without having to change the underlining core IT systems. Organizations worldwide have either started adopting or seeking to adopt RPA in order to transform their workplace to a happier one through freeing up more than 50% of their time which can be otherwise utilized for more complicated job. The study focuses on how organizations are replacing conventional way of managing variety of tasks with Robotic process automation. Specifically, the study attempts to find out if the organizations have indeed benefited by implementing RPA. Results highlight that organizations were able to generate enhanced employee experience, lower cost of operations, efficiency gains, quality and compliance, scalability and redeployment of people from mundane processes through adopting RPA.